Research on Conical Magnetorheological and Shape Memory Alloy Composite Transmission Performance - Xi Wang; Jin Huang; Yong Xie (Jixie chuandong)
In view of the disadvantage of magnetorheological fluid (MRF) performance degradation at high temperature, a conical MRF and shape memory alloy (SMA) hybrid transmission method is proposed. Based on the Bingham model, the rheological properties of MRF are described, and based on the thermal effect of shape memory alloy, the influence of temperature shape memory alloy spring output force is analyzed. The transfer torque equation of conical magnetorheological and SMA composite drive is established, and its driving mechanism is revealed. The results show that the transmission torque of conical magnetorheological drive decreases with the increase of conical angle. The torque transmitted by conical magnetorheological method is larger than that by disc magnetorheological method under the same magnetic field strength and transmission radius. The friction torque produced by the slider driven by SMA spring at high temperature can compensate for the deterioration of MRF performance and ensure the stable transmission performance of the transmission device.